Los pueblos originarios en el Bicentenario argentino (2010): ¿Hacia un reconocimiento nacional? - Natalia Molinaro (Les Cahiers ALHIM)
The history of the indigenous groups in the Argentine Republic is one of social, political and symbolic exclusion. To have a civic nation implied the homogenization of a heterogeneous population: “integrating” signified “rendering invisible”. This situation changed in the last decade of the twentieth century: in negotiations with the state and private companies, visibility became a key and essential tool. Visibility also gained greater importance as the legitimacy and role of the State weakened with the crisis the country suffered in the years 2001 – 2002. In this context of loss of values and meaning, the political and identity discourse of indigenous organizations began to find an important eco in argentine society. In 2010, the street show organized for the celebrations of the 25th of May by Buenos Aires, as well as the reception of indigenous delegations in the Casa Rosada, reflected a will to break with the historical traditional representation of the nation and a necessity to symbolically redefine citizenship.